Industrial H2-SCR of NO on a novel Pt/MgO–CeO2 catalyst - Efstathiou, Angelos M.; Costa, Costas; Savva, Petros G. (My University, 2007)
We describe here the performance of a novel MgO–CeO2-supported Pt (0.1 wt%) catalyst towards the selective conversion of NO into N2 (SN2 > 80%) by using H2 (H2-SCR) under process conditions similar to those encountered in the NH3-SCR in the low temperature range of 150– 200 8C. At 200 8C, 100% conversion of NO and 85% N2-selectivity were obtained with a feed stream containing 1000 ppm NO, 5% O2, 5%H2O, 10% CO2, 0–0.5% CO, and using 1.5% H2 in the feed as reducing agent (GHSV = 40,000 h-1). Thus, a N2-yield of 85% similar to that obtained in most NH3-SCR applications could make H2-SCR as the most environmentally friendly NOx control catalytic technology with great potential to replace the existing NH3-SCR technology. The latter is currently used industrially mainly in power and nitric acid plants, gas turbines, furnaces, boilers, and waste incinerators for the elimination of NOx. However, this technology faces several problems such as catalyst deterioration, emissions of non-reacted toxic NH3 (ammonia slip), ash odor, air-heaters fouling, and a high running cost.
Keywords: H2-SCR; NO reduction; Lean de-NOx; Supported-Pt catalyst